PENGARUH DIGITAL STORYTELLING TERHADAP KEPUTUSAN PEMBELIAN PRODUK EIGER PADA MARKETPLACE SHOPEE - Gugyh Susandy; Elsa Nursaadah (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2023)
Digital storytelling is one of the emerging marketing strategies, the power of storytelling has been widely recognized across disciplines including marketing Storytelling is more trusted than rational arguments, statistical data, and facts.         Decision making is an important topic in the field of marketing, which studies how individuals, groups and organizations choose, buy, use and utilize goods, services, ideas or experiences in order to satisfy their needs and desires.         The research objective is to find out digital storytelling on purchasing decisions for Eiger products on the shoppe marketplace. The research approach uses quantitative. The research method used is explanatory verification slot thailand research method with a quantitative approach. Sampling was done by purposive sampling. The sample in this study were students of Stie Sutaatmadja, Selangor Islamic University Malaysia and the General who are active users of the shopee marketplace, with a sample of 100 respondents. The results of this study indicate the results of the t test that the Digital Storytelling (X) tally shows that the significance level is 0.00 <0.05, which means that the hypothesis is accepted, so the Digital Storytelling (X) variable has an effect on the Purchasing Decision Performance variable (Y).